A new species of Shaanxispira (Bovidae, Artiodactyla) from the upper Miocene of China - Shi, Qinqin; He, Wen; Chen, Shanqin (Zootaxa, 2014)
A new species of the bovid Shaanxispira, from the upper Miocene deposits of the Linxia Basin, Gansu Province, China, is described here. Shaanxispira is endemic to Northern China and was previously known only from the Lantian area, Shaanxi Province, by two species, S. chowi and S. baheensis. The new species, S. linxiaensis nov. sp., is of early Bahean in age, slightly older than the species from the Lantian area. The horn-cores of the new species are more derived, with large wing-shaped antero-medial keels, suggesting the occurrence of a different lineage of Shaanxispira in the Linxia Basin. Although Shaanxispira has homonymously twisted horn-cores, it is not closely related to other late Miocene bovids with homonymously twisted horn-cores, like Oioceros and Samotragus. Its phylogenetic status is still in debate, but might be more closely related to the late Miocene “ovibovines.”